Akuntansi yang Bagaimana yang Mampu Meredam Sifat Materialistik? (IAIN Kudus, 2023)
The discovery of materialistic phenomena among accounting students is a form of the bad reality of conventional accounting education. This study aims to find out how accounting can reduce these characteristics in accounting students. Research using qualitative methods using grounded theory Methods of data collection through interviews, observation, and literature study to produce a theory. The results of the study show that sharia accounting, which is oriented towards immaterial aspects such as love and spirituality, is finally able to bring selfawareness and reduce the materialistic nature that has been embedded previously. In order to make it happen, non-mainstream sharia accounting topics are needed, which address the developing field of sharia accounting but have not yet been accommodated by a professional association. Through the appointment of this topic, it is also proven that science is not selfish because it does not stop at students but also talks back to the surrounding environment.